1975
DOI: 10.1063/1.430886
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer studies of Fe2+ in anhydrous hemoglobin and its isolated subunits

Abstract: The Mössbauer spectra of dehydrated αSH and βSH deoxyhemoglobin subunits were obtained over a temperature range from 77 to 200°K and compared with anhydrous hemoglobin spectra. The Mössbauer data for both subunits show a superposition of a ferrous high spin (S = 2) and a ferrous low spin (S = 0) quadrupole doublet of approximately equal intensity. No differences either in the isomer shifts or the quadrupole splittings were detected between the three hemoproteins. Consequently, the model for AHb–A with the α an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Dehydration of myoglobin (Mb) films starting with aqueous solutions-or suspensions-, or from the high humidity range, show that when the protein is dried below a critical water content irreversible changes are produced in the macromolecule. 8 Previous studies on Hb have shown that the dried protein forms a derivative optically [10][11][12][13][14] and magnetically 15,16 distinct from that observed in solution. This state is known as haemichrome or haemochrome depending if the haem iron is in the ferric or ferrous state respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration of myoglobin (Mb) films starting with aqueous solutions-or suspensions-, or from the high humidity range, show that when the protein is dried below a critical water content irreversible changes are produced in the macromolecule. 8 Previous studies on Hb have shown that the dried protein forms a derivative optically [10][11][12][13][14] and magnetically 15,16 distinct from that observed in solution. This state is known as haemichrome or haemochrome depending if the haem iron is in the ferric or ferrous state respectively.…”
Section: Introductionmentioning
confidence: 99%